Application of Advanced Platelet-Rich Fibrin in Oral and Maxillo-Facial Surgery: A Systematic Review - Marek Chmielewski; Andrea Pilloni; Paulina Adamska (Journal of Functional Biomaterials)
Background: Advanced platelet-rich fibrin (A-PRF) is produced by centrifuging the patient’s blood in vacuum tubes for 14 min at 1500 rpm. The most important component of A-PRF is the platelets, which release growth factors from their ⍺-granules during the clotting process. This process is believed to be the main source of growth factors. The aim of this paper was to systematically review the literature and to summarize the role of A-PRF in oral and maxillo-facial surgery. Materials and Methods: A systematic review was carried out, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (PROSPERO: CRD42024584161). Results: Thirty-eight articles published before 11 November 2024 were included in the systematic review. The largest study group consisted of 102 patients, and the smallest study group consisted of 10 patients. A-PRF was most often analyzed compared to leukocyte-PRF (L-PRF) or blood cloth. A-PRF was correlated with lower postoperative pain. Also, A-PRF was highlighted to have a positive effect on grafting material integration. A-PRF protected areas after free gingival graft very well, promoted more efficient epithelialization of donor sites and enhanced wound healing. Conclusions: Due to its biological properties, A-PRF could be considered a reliable addition to the surgical protocols, both alone and as an additive to bio-materials, with the advantages of healing improvement, pain relief, soft tissue management and bone preservation, as well as graft integration. However, to determine the long-term clinical implications and recommendations for clinical practice, more well-designed randomized clinical trials are needed in each application, especially those with larger patient cohorts, as well as additional blinding of personnel and long follow-up periods.